AKTIVITAS PROMOSI TOKO ABON MULIA DALAM MEMBANGUN BRAND AWARENESS - Yulia Pramudya Wardhani; Estu Widiyowati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This study aims to analyze the promotional activities carried out by Toko Abon Mulia in building brand awareness, particularly through the utilization of digital media such as Shopee and WhatsApp Business. Digital platforms have become an essential tool for SMEs to expand their market reach and introduce products more effectively. Shopee is used as an e-commerce platform that provides product catalogs, promotional features, and customer reviews, while WhatsApp Business serves as an interactive communication medium that strengthens relationships with customers. This research employed a qualitative descriptive approach with a case study design, using in-depth interviews with the owner, direct observations, and documentation of promotional activities. The findings reveal that the promotional activities of Toko Abon Mulia contribute to enhancing brand awareness by expanding product information reach, creating more personal consumer interactions, and building customer trust and loyalty. Consistent and integrated promotional activities, both through digital and offline media, have proven effective in strengthening Toko Abon Mulia’s brand image in a competitive market. Keywords: Promotional Activities, Brand Awareness, Shopee, SMEs, WhatsApp Business.